Techno-economic Optimization of Low Temperature CSP Systems Based on ORC with Screw Expanders. (May 2015) - Astolfi, M.
Abstract: Small Organic Rankine Cycles (ORC) coupled with low temperature parabolic collectors can be an affordable solution for the rural electrification of many remote areas worldwide. The aim of this work is to investigate the feasibility of this concept investigating the capabilities of different plant layouts and the use of volumetric screw devices as expander. Thirty working fluids are considered as possible candidates and all the solutions are optimized from a techno-economic point of view minimizing the specific cost of the plant. Finally a sensitivity analysis is carried out varying solar field specific cost and solar collector pressure drops.